Recommendations for designing reinforced concrete beams against low velocity impact loads - Wongmatar, P.; Hansapinyo, C.; Vimonsatit, V.; Chen, Wensu (World Scientific Publishing Co. Pte. Ltd., 2018)
This study investigates the behaviors of simply supported reinforced concrete (RC) beams subjected to impact loads. A numerical model of RC beams has been calibrated and a total of 18 RC beams with varying longitudinal reinforcement, transverse shear reinforcement, span and effective depth are investigated, subjected to different input impact energy. It is found that inertia force plays an important role in resisting an impact load at the starting time. The slenderness of the beam can cause increased downward reaction force and also amplifies the upward reaction force. Based on the numerical results, recommendations are made for designing RC beams under low velocity impact load. A formula is derived to predict the maximum mid-span deflection under low velocity impact load with respect to the kinetic energy and static bending capacity. The maximum spacing and the diameter of stirrups are also recommended so as to avoid the brittle failure under impact load.